Safety and effectiveness of dual therapy for Helicobacter pylori infection and the effect on the glycated hemoglobin level in type 2 diabetes - Jie Zhang; Xin Cao; Kai Ma; Yizhou Jiang; Xiangrong Qin; Xiaoyong Wang (Scientific Reports)
Abstract Patients with diabetes have a high risk of failure of H. pylori eradication therapy. The present study aims to evaluate the efficacy and safety of vonoprazan–amoxicillin (VA) dual therapy for the treatment of H. pylori infection in patients with type-2 diabetes mellitus (T2DM), and determine the influence of H. pylori eradication on the glycated hemoglobin A1C (A1C) level. The present prospective, single-center, single-arm, clinical trial enrolled 75 T2DM patients diagnosed with H. pylori infection. The patients were treated with the VA dual therapy regimen, which comprised of vonoprazan (20 mg, twice daily) and amoxicillin (750 mg, thrice daily), for 14 days (14-day VA dual therapy). The eradication rate in the intention-to-treat analysis and per-protocol analysis was 84.00% (63/75) and 87.14% (61/70), respectively. The multivariate analysis revealed that the independent risk factors for H. pylori eradication failure were smoking (OR: 4.59, 95% CI: 1.20–17.58, p = 0.026) and elevated A1C level (OR: 1.65, 95% CI: 1.01–2.68, p = 0.044). Patients in the successful eradication group presented with a significant decrease in the A1C level at 3 months, post-treatment, when compared to the pre-eradication level (7.70 ± 1.05% vs. 7.23 ± 1.00%, p = 0.006). VA dual therapy is a safe and effective regimen for patients with T2DM.